Práticas e ferramentas de aquisição de conhecimento para capacitação de competências do profissional técnico de TI - Garcia, Ruth Del Raso (2020)
The knowledge of an organization's employees is a resource that can increase the competitiveness of companies. However, the IT sector has been increasing and has presented a deficit of capacity in its workforce, including in terms of technical professionals. As a result, companies are looking to develop the skills (Knowledge, Skills and Attitudes) of their IT technical professionals. This research aims to identify the most effective knowledge acquisition practices and tools for training the skills of IT technical professionals. To this end, a quantitative descriptive research was developed, which was carried out by means of a single case study in a large and highly representative IT company in the Brazilian context. As a research tool, a quiz was developed applied to professional IT managers in the areas of technical support, systems’ development, networks and infrastructure of an IT company. From the results collected in this first research instrument, a second quiz was developed for application with the technical IT professionals, who work in the analyzed company as programmers, systems’ analysts/engineers or IT environments. As the main results of the research, the main practices for training the ‘dimension - knowledge’ were: brainstorming, mentoring, postaction review, corporate university and lessons learned. As for IT tools, the highlights were: VOIP telephony, advanced search tools, competitive intelligence, audit tools and document management systems. In addition, the main practices for training the ‘dimension - skills’ were: capturing ideas, corporate knowledge portals, organizational learning, managing customer relationships and best practices. As for IT tools, the following stand out: performance support system, web-based training, specialized systems, audit tools and collaborative virtual spaces. Finally, the main practices for training the ‘dimension - attitudes’ were: identification / acquisition of knowledge, knowledge and processes’ maps, organizational memory, best practices and organizational learning. As for IT tools, the following stand out: corporate portal, virtualization, collaborative virtual spaces, competitive intelligence and documents management systems. In summary, the ‘dimension - knowledge’ makes the IT professional skills aspect most impacted by the knowledge acquisition practices and tools analyzed; followed by the ‘dimension - skills’ and, finally, the ‘dimension – attitudes’. As a conclusion, the results verified in this work show the relevance of Knowledge’s Management, as well as its practices and tools, for IT’s professionals training. In addition, the results indicated can also support companies to provide a better view of how these practices and tools are interpreted by those who use them, that is, the IT’s managers and technical professionals involved.